Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1973
DOI: 10.1037/h0035772
|View full text |Cite
|
Sign up to set email alerts
|

Prototype abstraction and classification of new instances as a function of number of instances defining the prototype.

Abstract: Ease of prototype abstraction and recognition of new instances belonging to the prototype was facilitated by increasing the number of instances sorted together during original learning. The 5s sorted distorted dot patterns into groups of 3, 6, and 9 instances, each group containing distortions generated from a single prototype. Following the sorting task, half of the 5s were tested immediately on their ability to correctly classify old and new patterns as well as the prototype; another group of 5s was tested 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

21
130
1

Year Published

1980
1980
2009
2009

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(153 citation statements)
references
References 6 publications
21
130
1
Order By: Relevance
“…In addition, the prototypicality of the foils presented in the recognition task was a significant factor in recognition performance: More prototypical foils were more likely to be incorrectly recognized than were less prototypical foils. Finally, it was shown that the learning prooedure produced the same effect of category size on classification that had been obtained previously by Homa et al (1973). Classification of new exemplars was enhanced by increasing the number of exemplars representing a category during learning.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In addition, the prototypicality of the foils presented in the recognition task was a significant factor in recognition performance: More prototypical foils were more likely to be incorrectly recognized than were less prototypical foils. Finally, it was shown that the learning prooedure produced the same effect of category size on classification that had been obtained previously by Homa et al (1973). Classification of new exemplars was enhanced by increasing the number of exemplars representing a category during learning.…”
Section: Discussionsupporting
confidence: 64%
“…Since classification of new items and the prototype remained constant across the delay, the authors suggested that their classification was mediated, not by the deteriorating information about the learning exemplars, but by the abstracted prototypical representation, which had been maintained. The findings of Posner and Keele have been expanded by Homa and his colleagues (Homa, Cross, Cornell, Goldman, & Shwartz, 1973), who showed that classification of new exemplars can be influenced by the number of exemplars that represent the category during learning. When subjects were taught to classify three categories represented by three, six, and nine exemplars, transfer to new items increased with the size of the learning set.…”
mentioning
confidence: 95%
“…The assumption of all-or-none forgetting of features borrows from Bower's (1967) multicomponent theory of the memory trace, and this suggests that some version of that theory would predict the behavior shown in the present simulations. What we have demonstrated most clearly here is that differential forgetting of prototypes and old exemplars, as shown by Homa et al (1973), Posner and Keele (1970), and Strange et al (1970), cannot be taken as conclusive evidence for the abstraction of a prototype during classification learning, for there is at least one set of assumptions that predicts this result purely from the forgetting of old exemplars, with no ad hoc mechanisms required. Our findings thus provide added support for the notion that classification learning may be based solely on memory for past instances, without involving the representation of a prototype or abstract idea.…”
Section: Discussionmentioning
confidence: 95%
“…The most compelling evidence for this conclusion has come from studies comparing changes over a retention interval in classification performance on exemplars and on the prototypes from which the exemplars were derived. Specifically, several studies have shown that the ability to classify old exemplars declines substantially over time, whereas the ability to classify prototypes, not seen during origina11earning, declines little and in some cases may even improve (Homa, Cross, Cornell, Goldman, & Schwartz, 1973;Posner & Keele, 1970;Strange, Kenney, Kessel, & Jenkins, 1970). This differential forgetting suggeststhat the prototype has a representation of its own.…”
mentioning
confidence: 99%
“…In well-defined categorizations, transfer performance is nearly perfect and improves slightly with the distance between the to-be-categorized exemplar and the category boundary (see, e.g., Nosofsky, 1991; Vandierendonck, 1988Vandierendonck, , 1991. If the categorization is fuzzy, transfer performance is not quite so good, and it varies as a function ofthe similarity between the new exemplar and the old stimulus patterns (see, e.g., Homa, Cross, Cornell, Goldman, & Schwartz, 1973;Medin & Schaffer, 1978;Nosofsky, 1984Nosofsky, , 1986. In fact, it seems that transfer gradients occur with both kinds of category structure.…”
mentioning
confidence: 99%